Neurodevelopmental disorders and anti-epileptic treatment in a patient with a SATB1 mutation: A case report - Yu, Ying; Li, Cuiyun; Li, Wei; Chen, Liting; Wang, Dan; Wang, Jie; Wang, Jian; Yao, Ruen (Frontiers in Pediatrics, 2022)
Variants of SATB1 causing developmental delay with dysmorphic facies and dental anomalies have been reported in a small cohort. Epilepsy is presented by most patients as a main clinical feature during neurodevelopment; however, its treatment information is unknown. Here, we present a Chinese patient with a de novo truncating variation in SATB1, who presented with mild developmental delay. We disclose the detailed anti-epileptic pharmacological treatment that enabled a favorable outcome. Our study provides important information that may aid clinicians in the prognosis and treatment of rare neurological developmental disorders caused by gene mutations.